2015
DOI: 10.1111/1471-0528.13506
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic nerve injury negatively impacts female genital blood flow and induces vaginal fibrosis—implications for human nerve‐sparing radical hysterectomy

Abstract: Objective This study sought to develop a novel animal model to study the impact of nerve-sparing radical hysterectomy (NSRH) on female genital blood flow.Design In vivo animal study.Population Thirty Sprague-Dawley female rats.Materials and methods Female rats underwent either unilateral pelvic nerve (PN) crush (PNC; n = 9), or crush of both the PNs and all efferent nerves in the pelvic plexus ('clock-nerve crush', CNC; n = 9). Under anaesthesia, we electrically stimulated the crushed PN at 3 and 10 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The penile midshaft at the level of the injection site was harvested, fixed, and further processed for histology. Haematoxylin and eosin and Masson's trichrome staining procedures were performed according to a standard protocol, previously described .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The penile midshaft at the level of the injection site was harvested, fixed, and further processed for histology. Haematoxylin and eosin and Masson's trichrome staining procedures were performed according to a standard protocol, previously described .…”
Section: Methodsmentioning
confidence: 99%
“…Glyceraldehyde‐3‐phosphate dehydrogenase (GADPH) was used as an internal standard. Primary antibodies were Rb anti‐collagen III (1:1 000; Abcam Inc., Cambridge, MA, USA), Ms anti‐elastin (1:500, Abcam) and Rb controls against GADPH (1:1 000, Santa Cruz Biotechnology, Santa Cruz, CA, USA), Rb anti‐collagen I (1:500; Abcam Inc.) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 Medical interventions that disrupt the APNs (eg, radical hysterectomy and proctolectomy with ileo pouch-anal anastomosis) impair female genital response, manifested as lower vaginal blood flow in response to an erotic film. 13,14,53 In addition, Castiglione et al 54 found impaired genital blood flow in female rats after neuropraxia of the APN (ie, nerve damage caused by a physiological block of nerve conduction within an axon, such as from compression or stretching of the nerve). Therefore, it is plausible that compression of the fetal head during the second stage of labor, which is associated with pudendal nerve damage during childbirth, may also play a role in damage to the APNs.…”
Section: Lower Genital Response After Vaginal Birthmentioning
confidence: 99%
“…Western blot was performed as previously described [21][22][23] for the detection of collagen I, collagen III, and elastin proteins at the level of the penile midshaft. Glyceraldehyde-3-phosphate dehydrogenase or Beta-Actin were used as an internal standard.…”
Section: Western Blot Analysismentioning
confidence: 99%